Single Step Grown NiFe Sponges as Efficient Water Splitting Electrocatalysts in Alkaline Medium. Issue 4 (27th January 2020) - Thoufeeq, S.; Rastogi, Pankaj Kumar; Thomas, Senoy; Shravani, Anagandula; Narayanan, Tharangattu N.; Anantharaman, M. R.
Abstract: Catalysts for heterogeneous catalytic reactions, particularly for total water splitting, is receiving tremendous attention and sustainable fuel development is highly relied on the catalysts development, where both the material and its method of preparation are important. Here, bimetallic multi‐phasic catalysts containing nickel (Ni) and iron (Fe) are synthesized using a simple but reproducible polyol method, which results in to different sponges having control over their chemical stoichiometry. The macroporous sponges thus developed contain metallic Ni, NiO, and Fe2 O3, where their proportionate content can be varied with initial precursor ratio. The NiFe15 so developed is having the best oxygen evolution performance in terms of overpotential, kinetics, and charge transfer properties, and it is found to be better than the benchmarked IrO2 based catalysts. The hydrogen evolution from the other ratio, NiFe5, is found to be better than other Ni and Fe based samples, and it is found to be very close to the hydrogen evolution performance of platinum. An alkaline water electrolysis full cell is constructed, devoid of any precious metals but with NiFe5 and NiFe15, and the overall splitting potential for the benchmarked current density of 10 mAcm −2 is found to be 1.62 V only, which is better or on par with the other singly/multi‐phasic systems reported so far. Hence the work presented here shows the possibilities of futuristic electrochemical technologies with viable catalysts, and a detailed study is presented. Abstract : A facile method is demonstrated to obtain nickel and iron based porous sponges, where by varying their precursor ratio, total water splitting electrocatalysts can be developed. The NiFe based sponges are found to be efficient in water electrolysis and on par with some of the benchmarked catalysts so far reported.